Prison education across Europe: policy, practice, politics (UCL Press, 2014)
The nature of the education offered in prisons varies greatly. Provision can be focused narrowly on limited objectives, such as training for employment or seeking to 'address offending behaviour'. On the other hand, where prison education follows the policies of the Council of Europe or the European Union, which are drawn from the traditions of adult education and life-long learning, it becomes a more comprehensive and transformative experience for men and women held in prison. Underpinning these different approaches are two very different perceptions of those held in prison: one sees merely 'an offender', while the other recognizes 'the whole person' and his or her membership of society. Where narrow and negative concepts of the men and women held in prison prevail, one tends to find severe limitations on the quality and quantity of the education offered. Four such 'curtailments' are discussed.